2020
DOI: 10.3390/membranes11010019
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Fabrication of Organic Solvent Nanofiltration Membranes

Abstract: Organic solvent nanofiltration (OSN) has been considered as one of the key technologies to improve the sustainability of separation processes. Recently, apart from enhancing the membrane performance, greener fabricate on of OSN membranes has been set as a strategic objective. Considerable efforts have been made aiming to improve the sustainability in membrane fabrication, such as replacing membrane materials with biodegradable alternatives, substituting toxic solvents with greener solvents, and minimizing wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 55 publications
(124 reference statements)
0
14
0
Order By: Relevance
“…Phase inversion-generated nanocomposite membranes have been used for nanofiltration, microfiltration, or ultrafiltration processes. The choice of solvent used in the phase inversion technique may cause a better dispersion of the graphene and GO nanoparticles in the polymer matrices [110,111].…”
Section: Polymer/graphene Nanocomposite Membranes For Water Permeationmentioning
confidence: 99%
“…Phase inversion-generated nanocomposite membranes have been used for nanofiltration, microfiltration, or ultrafiltration processes. The choice of solvent used in the phase inversion technique may cause a better dispersion of the graphene and GO nanoparticles in the polymer matrices [110,111].…”
Section: Polymer/graphene Nanocomposite Membranes For Water Permeationmentioning
confidence: 99%
“…where is the effective pore radius (membrane) and is the Stokes radius of ion i. Finally, by substituting Equations ( 9), ( 13)-( 16) into Equations ( 3) and ( 7), we obtained the following equations (Equation (18) and Equation ( 19)):…”
Section: Model Equationsmentioning
confidence: 99%
“…Thus, W. Shao et al recently synthesized an NFM using polyethyleneimine as the aqueous reactive monomers, and a positively charged thin-film nanocomposite NFM with enhanced performance was developed by successfully incorporating graphene oxide (GO) into the substrate active layer [17]. Other remarkable works are also reported, including that performed on organic solvent NFMs and remineralization of desalinated water [11,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, one-step membrane surface modifications by Fu et al (2021) was found to improve the permeation of nonpolar solvent while maintaining high rejections of solutes. Therefore, the encouraging performance and process development of OSN membranes have provided researchers with confidence to explore OSN implementation in various industries (Marchetti et al, 2014;Nguyen Thi et al, 2021;Szekely et al, 2014). As of current, OSN has found numerous uses for molecular-scale separation including the recovery of homogeneous catalyst (Peddie et al, 2017), solvent recovery (Rundquist et al, 2012), chiral separation (Ghazali et al, 2006), concentration of natural extracts (Peev et al, 2011;Peshev et al, 2011), purification of pharmaceuticals (Székely et al, 2011) and peptide synthesis (So et al, 2010).…”
Section: Introductionmentioning
confidence: 99%